ANALISIS SIKAP KONSUMEN TERHADAP ATRIBUT PRODUK KOPI RIGIS (Studi Kasus: BUMDES Kampung Kopi Rigis, Pekon Rigis Jaya, Kecamatan Air Hitam, Kabupaten Lampung Barat) - Arisandi, Dimas Ferdian; Al Rasyid, Harun; Hasanudin, Udin; Sartika, Dewi (Jurnal Agroindustri Berkelanjutan, 2023)
Kampung Kopi is a company that runs in processing various types of coffee products, with the name of the product is Kopi Rigis. Kopi Rigis is a ground coffee product that is still developing with product distribution still limited to certain areas. Therefore, this research was conducted to determine consumer attitude towards the attributes of Kopi Rigis to be used as a consideration for product development strategy. This research was conducted using the Fishbein Multiattribute method to determine the level of consumer belief and evaluation, also the importance performance analysis method to determine the level of importance and performance level of consumers on the attributes of Kopi Rigis products. The results of the attitude scores for each attribute are; 16.20 for the taste, 17.34 for the aroma, 12.84 for the variant, 15.38 for the price, and 14.83 for the packaging. While the results of the importance performance analysis shows the attributes of Kopi Rigis obtained a total value of 20.57 for the importance level and 15.58 for the performance level. Consumer attitudes as a whole attribute of Kopi Rigis is neutral with a total attitude value of 76.59. The taste and aroma attributes were assessed positively with an attitude value of 16.20 for the taste attribute and 17.34 for the aroma attribute. Meanwhile, the variant, price, and packaging attributes showed a neutral attitude with an attitude value of 12.84 for the variant attribute, 15.38 for the price attribute, and 14.83 for the packaging attribute. Attributes of Kopi Rigis that included in Quadrant I are the price, because these attribute are considered important in influencing consumers to buy the products and it is requiring an adjustment. The taste and aroma are included in Quadrant II, while the variant and packaging are included in Quadrant III.